Central Neuropathic Pain in Multiple Sclerosis Is Associated with Impaired Innocuous Thermal Pathways and Neuronal Hyperexcitability. Issue 10 (18th March 2021) - Rivel, Michal; Achiron, Anat; Dolev, Mark; Stern, Yael; Zeilig, Gabi; Defrin, Ruth
Abstract: Objective: About one-third of patients with multiple sclerosis (MS) suffers from chronic and excruciating central neuropathic pain (CNP). The mechanism underlying CNP in MS is not clear, since previous studies are scarce and their results are inconsistent. Our aim was to determine whether CNP in MS is associated with impairment of the spinothalamic-thalamocortical pathways (STTCs) and/or increased excitability of the pain system. Design: The study was cross-sectional Setting: The study was conducted at a general hospital Participants: Participants were 47 MS patients with CNP, 42 MS patients without CNP and 32 healthy controls. Methods: Sensory testing included the measurement of temperature, pain, and touch thresholds and the thermal grill illusion for evaluating STTCs function and hyperpathia and allodynia as indicators of hyperexcitability. CNP was characterized using interviews and questionnaires. Results: The CNP group had higher cold and warm thresholds ( P < 0.01), as well as higher thermal grill illusion perception thresholds ( P < 0.05), especially in painful body regions compared with controls, whereas touch and pain thresholds values were normal. The CNP group also had a significantly greater prevalence of hyperpathia and allodynia. Regression analysis revealed that whereas presence of CNP was associated with a higher cold threshold, CNP intensity and the number of painful body regions were associated with allodynia and hyperpathia, respectively. Conclusions: CNP in MS is characterized by a specific impairment of STTC function, the innocuous thermal pathways, and by pain hyperexcitability. Whereas CNP presence is associated with STTC impairment, its severity and extent are associated with pain hyperexcitability. Interventions that reduce excitability level may therefore mitigate CNP severity.